Behavioral therapy for urinary symptoms in Parkinson's disease: A randomized clinical trial. Issue 6 (11th June 2019) - Vaughan, Camille P.; Burgio, Kathryn. L.; Goode, Patricia S.; Juncos, Jorge L.; McGwin, Gerald; Muirhead, Lisa; Markland, Alayne D.; Johnson, Theodore M.
Abstract: Aim: Determine the efficacy of behavioral therapy for urinary symptoms in Parkinson's disease. Methods: Randomized trial of behavioral therapy compared with control condition among adults (aged 54‐85 years, 74% male, 10% Black/ 83% White) with Parkinson's and greater than or equal to 4 incontinence episodes weekly. Behavioral therapy included pelvic floor muscle exercises, bladder training, fluid and constipation management. Both groups completed bladder diary self‐monitoring. Outcomes included diary‐derived incontinence and ICIQ‐overactive bladder (OAB) score (range, 0‐16) with bother and quality of life questionnaires (higher scores = worse outcomes). Results: Fifty‐three participants randomized and 47 reported 8‐week outcomes including 26 behavioral therapy and 21 control. Behavioral vs control participants were similar with respect to age (71.0 ± 6.1 vs 69.7 ± 8.2 years), sex (70% vs 78% male), motor score, cognition, mean weekly incontinence episodes (13.9 ± 9.6 vs 15.1 ± 11.1) and OAB symptoms (8.9 ± 2.4 vs 8.3 ± 2.2). Weekly incontinence reduction was similar between behavioral (−6.2 ± 8.7) and control participants (−6.5 ± 13.8) ( P = 0.89). After multiple imputation analysis, behavioral therapy participants reported statistically similar reduction in OAB symptoms compared to control (−3.1 ± 2.8 vs −1.9 ± 2.2, P = 0.19); however quality of life (−22.6 ± 19.1 vs −7.0 ± 18.4, P = 0.048) and bother (−12.6 ± 17.2 vs − 6.7 ± 8.8, P = 0.037) improved significantly more with behavioral therapy. Conclusion: Self‐monitoring resulted in fewer urinary symptoms; however, only multicomponent behavioral therapy was associated with reduced bother and improved quality of life. Providers should consider behavioral therapy as initial treatment for urinary symptoms in Parkinson's disease.